Women footballers in Indochina: a place in the stadium? - Fossard, B. (Soccer & Society, 2024)
Indochinese women footballers proclaim a degree of liberty and very considerable autonomy; they thus play an essential role in extending women`s emancipation in Indochina. They aim to gain a level of social and human dignity enabling women to assert themselves through an identity of gender more than of social status. This article examines the social, economic and political background of the emergence of the active female figure in the sporting world of Indochina vis-a-vis its European counterpart. It also addresses the debates on the question of women`s liberation or emancipation through sport alias football in Vietnamese society.